Shop drawing of additional door SF11-SF12 (RFA - 027_Rev-A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.